(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2021)
The practice of moral judgement in historiography is a topic in critical philosophy of history. In general, there are two opinions on the practice of moral judgement in history: firstly, those who are against it, such as Croce, Bloch and Butterfield; secondly, those who are in support of it, such as Lord Acton, Ibn Khaldun and al-Biruni. Understanding the practice is crucial in facilitating “intellectual serenity” among historians in deciding on their research method. This article discusses al-Biruni’s position and epistemic justification on the issue of moral judgement in research in history. The analysis of al-Biruni’s perspective, based on his book, al-Athar al-Baqiyah ‘an al-Qurun al-Khaliyah, shows that his epistemic justification on moral judgement in history was influenced by his religious tradition.